Building HIV healthcare worker capacity through telehealth in Vietnam. Issue 4 (8th April 2020) - Pollack, Todd M; Nhung, Vo Thi Tuyet; Vinh, Dang Thi Nhat; Hao, Duong Thi; Trang, Le Thi Thu; Duc, Pham Anh; Kinh, Nguyen Van; Dung, Nguyen Thi Hoai; Dung, Duong Lan; Ninh, Nguyen Thi; Huyen, Ho Thi Thanh; Huy, Vo Xuan; et al.
Abstract : Development of a robust technical assistance system is an essential component of a sustainable HIV response. Vietnam's National HIV Program is transitioning from a largely donor-funded programme to one primarily supported by domestic resources. Telehealth interventions are increasingly being used for training, mentoring and expert consultation in high-resource settings and hold significant potential for use as a tool to build HIV health worker capacity in low and middle-income countries. We designed, implemented and scaled up a novel HIV telehealth programme for Vietnam, with the goal of building a sustainable training model to support the country's HIV workforce needs. Over a 4-year period, HIV telehealth programmes were initiated in 17 public institutions with participation of nearly 700 clinical sites across 62 of the 63 provinces in the country. The telehealth programme was used to deliver certificate training courses, provide clinical mentoring and case-based learning, support programme implementation, provide coaching in quality improvement and disseminate new guidelines and policies. Programme evaluation demonstrated improved health worker self-reported competence in HIV care and treatment and high satisfaction among the programme participants. Lessons learnt from Vietnam's experience with telehealth can inform country programmes looking to develop a sustainable approach to HIV technical assistance and health worker capacity building.